Introducing New Traditional Cuisine for Maintaining Culture and Promoting Tourism in Tegal Regency - Ayu Ida Savitri (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
Culture is the custom, the art, the specific institution, and the achievement of a particular nation, people, or social group. Since a culture reflects the life of its owner, when the owner of a culture no longer keeps the culture, it becomes a history. One of ways of maintaining culture is through developing new ones, such as developng new tradition. One of the examples of it is developing new tradition of cooking traditional cuisine especially made by local people using local ingredient with new way of consuming it. This research shows how the local people of Tegal Regency develops new traditional cuisine from the old one, supported by the local govenment to be part of their culinary tourism promotion. The first one is sate blengong, a side dish developed from the old/original chicken/lamb satay but was made of blengong meat, a cross breed of bebek (duck) and mentok (Muscovy duck), sticked on bamboo skewer, grilled and served with peanut sauce. The second one is Rujak Teplak, a side dish developed from the old/original rujak (boiled vegetables served with peanuts sauce) whose name is created from the way the seller put nine kinds of vegetable on banana leaf as its wrapping (teplak means putting something with a force resulting a kind of slapping sound). The result shows that the new traditional cuisines are famous for its uniqueness and good taste so that it attracts tourists to come and taste it after seeing them being promoted through various social medias. It can be concluded that those new cuisines keeps Tegal Regency’s culinary tradition as part of their culture that is beneficial to promote Tegal Regency culinary tourism.Keywords: culture, tradition, cuisine, culinary, tourism, promotion